2015
DOI: 10.1101/031492
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fast and accurate construction of confidence intervals for heritability

Abstract: Estimation of heritability is fundamental in genetic studies. In recent years, heritability estimation using linear mixed models (LMMs) has gained popularity, because these estimates can be obtained from unrelated individuals collected in genome wide association studies. Typically, heritability estimation under LMMs uses either the maximum likelihood (ML) or the restricted maximum likelihood (REML) approach.Existing methods for the construction of confidence intervals and estimators of standard errors for both… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Furthermore, the heritability estimates from the constrained REML algorithm are potentially biased due to the bounded variance component parameter space, which is alleviated by the reporting of the estimates from the unconstrained REML algorithm. Schweiger et al 42 showed that the reported standard errors from the constrained REML algorithm led to the construction of confidence intervals with inaccurate coverage probabilities. However, the reported mean standard error from the constrained REML algorithm is a meaningful measure of the uncertainty in these estimates due to the law of large numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the heritability estimates from the constrained REML algorithm are potentially biased due to the bounded variance component parameter space, which is alleviated by the reporting of the estimates from the unconstrained REML algorithm. Schweiger et al 42 showed that the reported standard errors from the constrained REML algorithm led to the construction of confidence intervals with inaccurate coverage probabilities. However, the reported mean standard error from the constrained REML algorithm is a meaningful measure of the uncertainty in these estimates due to the law of large numbers.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore first asked whether biome-explainability can be reliably estimated with our sample size. To this end, we computed confidence intervals (CIs) for a large number of biome-explainability values via parametric bootstrap, which constructs CIs by repeatedly drawing random realizations of the phenotypes according to the principle of test inversion 48 . We find that biome-explainability can be estimated more accurately than genetic heritability in our sample, with an average 95% biome-explainability CI width of 32.8% (averaged over different biome-explainability levels), compared with 98.7% for a genetic heritability CI in our cohort ( Supplementary Table 11).…”
Section: Biome-explainability Can Be Assessed More Accurately Than Gementioning
confidence: 99%
“…Since the distribution of the estimator is unknown, U cannot be inferred analytically and has to be estimated by a Monte-Carlo simulation. The straight forward way to carry such a simulation is to interpolate sample quantile of Θ(X), as in Schweiger et al [2016]. This approach is briefly described in Algorithm 1, resulting inÛ -an estimate of U .…”
Section: Why Test Inversionmentioning
confidence: 99%